Mastering derivatives simplify the complex / Aishah Mahat ... [et al.] - Mahat, Aishah; Putra, Muhamad Yadiy; Abd Naddin, Ahmad Fawzan; Shahrin, Ikhwan Syahmi; Mohd Nopiah, Zulkifli (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
This e-book, Mastering Derivatives: Simplify the Complex! aimed to help students in Calculus subject. Targeted users for this e-book are students who take foundation course. Mathematical tips and formulas will be placed in accordance with the subtopics whilst each question will be displayed based on the syllabus carried out during the lesson. At the end of each topic, targeted students should meet up with the lecturer to discuss over the solution of mathematics problem. With the existence of this e-book, hopefully it will be beneficial and give positive impact towards teaching and learning for students and lecturers.